Securitizing the Unseen: Behind Trump’s Reliance on Mexico in Combating Irregular Immigration - Eiga Sitompul; Bambang Cipto (Department of International Relations, Faculty of Social and Political Science, Universitas Airlangga, 2023)
This research aims to analyze the reasons behind Trump’s decision to pressure Mexico to combat irregular immigration. Trump’s administration showed an exceptional commitment to immigration control and dramatically re-oriented the immigration control mechanism in the United States (US). Despite unprecedented amounts of changes in the US internal immigration system under Trump, his presidency relied on Mexico for his securitization cause. Due to massive migration activities along the US-Mexico border, Trump forced Mexican authorities to cooperate with US institutions to reduce and filter migrant flows coming to the US. Nonetheless, existing literature regarding US immigration did not explain the reason behind Trump’s reliance on Mexican authorities and its cooperation system; thus this article aims to fill the gap. This research applies the migration securitization framework in evaluating the US immigration system prior to the 2019 US-Mexico joint statement on immigration. Using Bourbeau’s migration securitization framework, the research found that Trump’s immigration policy faced barriers due to interference from the opposition party. This research concluded that the US federal system and political climate confined Trump’s immigration enforcement efforts, thus pushing the administration to burden Mexican authorities with its enforcement efforts. Keywords: irregular immigration, Mexico, migration securitization, Trump, US. Penelitian ini bertujuan untuk menganalisis keputusan presiden Trump dalam menekan Meksiko untuk memerangi imigran gelap. Pemerintahan Trump menunjukkan komitmen luar biasa dalam mengontrol sistem imigrasi di Amerika Serikat (AS), mengorientasikan mekanisme imigrasi internal secara dramatis. Namun, terlepas dari perubahan besar dalam mekanisme imigrasi dibawah pemerintahan Trump, presiden Trump bergantung terhadap pemerintah Meksiko dalam mengimplementasikan agenda sekuritisasinya. Karena aktivitas migrasi besar-besaran di sepanjang perbatasan AS-Meksiko, Trump memaksa otoritas Meksiko untuk bekerja sama dalam menyaring arus migran yang datang ke AS. Studi-studi sebelumnya tidak menjelaskan alasan dibalik ketergantungan Trump pada otoritas Meksiko, sehingga artikel ini bertujuan mengisi kekosongan tersebut. Penelitian ini menerapkan kerangka sekuritisasi imigrasi dalam mengevaluasi sistem imigrasi AS sebelum pernyataan bilateral AS-Meksiko tahun 2019 tentang imigrasi. Menggunakan kerangka Sekuritisasi Bourbeau, penelitian ini menemukan bahwa kebijakan imigrasi Trump terhambat oleh campur tangan partai oposisi. Penelitian ini menyimpulkan bahwa sistem federal dan iklim politik di AS membatasi upaya penegakan imigrasi Trump, sehingga mendorong pemerintahan untuk membebani pemerintah Meksiko dengan upaya penegakannya. Kata-kata Kunci: Amerika Serikat, imigrasi ilegal, Meksiko, sekuritisasi imigrasi, Trump